Sleep Duration in Adolescence and Its Prenatal, Perinatal, and Health Determinants in a Large Population-based Cohort Followed from Birth - Berrutti, Barbara; Otero Xavier, Mariana; S. Santos, Iná; Matijasevich, Alicia; Tovo-Rodrigues, Luciana (Sleep Science, 2023)
Objective To investigate sleep duration and its associated factors in adolescents aged 11 years from the 2004 Pelotas (Brazil) Birth Cohort Study.Methods Sleep duration was assessed using a self-report sleep habits. Independent variables included perinatal, sociodemographic, behavioral, and health characteristics. The associations were estimated using multiple linear regression.Results The mean sleep duration of 3,179 adolescents was 9.3 hour (SD =1.7 hour). Longer sleep duration was associated with lower socioeconomic status at birth (β: 0.37, 95% CI: 0.12; 0.61), lower mother's education level (p < 0.001), and being female (β: 0.19, 95% CI: 0.06; 0.33). Shorter sleep duration was associated with cesarean section delivery (β: −0.16, 95% CI: −0.31; -0.02); having classes in the morning shift (β: −1.38, 95% CI: −1.51; -1.26), and lower terciles of physical activity (p = 0.04).Conclusions The mean sleep duration observed in this study was consistent with the international recommendations for this age range. Adolescents from lower income families, who are more active, study in shifts other than morning, girls, and those born through vaginal delivery presented higher sleep duration than their counterparts.
Keywords: sleep; adolescent; sleep deprivation; epidemiology